Exploring Mendeley-based thesis supervision model to avoid plagiarism - Andi Anto Patak; Muhammad Tahir; Andi Sahtiani Jahrir (Institute of Advanced Engineering and Science, 2022)
This study explored Mendeley-based thesis supervision models to avoid plagiarism. The focus of this study was four issues: i) Selecting the topic and deciding the thesis title; ii) Browsing and managing references; iii) Validating references; and iv) Matching ideas between the students’ arguments and citing other authors’ statements. This study employed a qualitative method with a case study design to explore an in-depth understanding of the Mendeley-based thesis supervision model to avoid plagiarism. Researchers posted a call for an interview in social media group for an English as a Foreign Language (EFL) lecturer in South Sulawesi, Indonesia. There were 15 EFL lecturers applied, but only four met the criteria. The criteria for choosing the participant are based on the Mendeley presentation experience, full-time teaching career, and willingness to participate in virtual interview sessions. There were two participants from a public university, one was from a private university, and the other was from a state Islamic university. A semi-structured interview technique was applied in this study. This study employed thematic analysis to explore participants' responses. This study reported that supervisors experienced different cases from the four items identified in this study. They are: i) Selecting the topic and deciding the thesis title, ii) Browsing and managing references; iii) Validating references; and vi) Matching ideas between the students' arguments and citing other authors’ statements.